Improving Biosecurity through Instructional Crisis Communication: Lessons Learned from the PEDv Outbreak - Timothy L. Sellnow; Jason S. Parker; Deanna D. Sellnow; Robert S. Littlefield; Emily M. Helsel; Morgan C. Getchell; Julia M. Smith; Scott C. Merrill (Journal of Applied Communications, 2017)
Crises, by their nature, demand effectively designed and quickly delivered instructional messages that compel stakeholders to take appropriate actions to protect themselves and their assets. The challenges of crisis communication are intensified in crises involving unanticipated and relatively unknown disease outbreaks with the potential to spread exponentially. This study assesses the communication challenges and opportunities in such volatile crises through an analysis of the Porcine Epidemic Diarrhea virus (PEDv) outbreak that severely threatened the United States pork industry in 2013 and 2014. Interviews were conducted with 13 individuals directly involved in developing and distributing risk and crisis biosecurity messages during the PEDv outbreak. Participants were selected based on affiliation with the National Pork Board, American Association of Swine Veterinarians, university extension, or their swine industry expertise. Four generalizable implications emerged: 1) the advantage of maintaining flexibility in crisis communication planning; 2) the value of audience analysis and message adaptation; 3) the importance of understanding not only what to do, but also why the recommended actions are essential; and 4) the utility of risk/crisis communication and education both prior to and during a crisis event.
Keywords: Crisis Communication; Risk Communication; Biosecurity; Instructional Communication